Dotazníkový prieskum manažmentu rizika na Slovensku - Varcholová, Tatiana (Univerzita Pardubice, 2004)
The article deals with the research of the enterprise risk management (ERM) in Slovak firms. When we compare the enterprise of developed economies with ours, we can see that in most enterprises there is the absence of ERM. The results of the research show the fact tahat some entrepreneurs do not deal at all with the risk in business - most of them just estimate the risk. Therefore Slovak managers have to reconsider their attitudes towards the evaluation of risk.
Keywords: manažerské rozhodování; rizikové faktory; průzkum trhu; Slovensko